Prevalence of smartphone addiction and the impact on sleep quality among undergraduate students at School of Health Sciences, USM - Othman, Nurul Aina (Universiti Sains Malaysia, 2023)
Smartphone is becoming a vital piece required technology, yet many people are getting addicted to it. It has been reported that late-night smartphone use, and addiction decrease the quality of sleep. Numerous studies have been done on sleep quality, but very few have linked it to smartphone addiction. A cross-sectional survey was carried out to study Prevalence of Smartphone Addiction and the Impact on Sleep Quality Among Undergraduate Students at School of Health Sciences, USM using a set of self-administered online questionnaire that adopted the Smartphone Addiction Scale (SAS) and Pittsburgh Sleep Quality Index. A total 289 undergraduate students in USM who fulfilled the inclusion and exclusion criteria were included in this study. Data were statistically analysed using the SPSS software version 26.0. Descriptive and Pearson’s Chi-Square were used for data analysis. The results show that 151 (52.2%) of the respondent were addicted to. Meanwhile, for the sleep quality, result revealed majority of the respondents 261 (90.3%) were poor sleepers. There was a significant association between smartphone addiction score and sleep quality score (p=0.002), that 144 (49.8%) of those addicted to smartphone usage were also experienced poor sleep quality. In conclusion, smartphone addicted is prevalence in this study. Social awareness campaigns about smartphone addiction and its impact on sleep quality are needed.